Crisis of the Doha cycle of multilateral trade negotiations and EU: Developing countries relations - Stevović Jelena (Međunarodni Problemi)
The author deals with the new cycle of multilateral trade negotiations that started in Doha in 2001. Since then, the main question has remained to be how to overcome the radically different priorities of developed and developing countries. EU insists on expanding the WTO regulation system. Developing countries were against broadening of the negotiations, especially not to development that is not directly related to the trade dimension. The clash appeared in the form of a crisis of the multilateral system but also in the form of a crisis of confidence in WTO. The general agreement signed by the members of WTO in July 2004 was of great importance for the future of multilateralism. It remains to be seen if that will be confirmed at the conclusion of the Doha cycle envisaged for the end of 2006.